Allocation of hunting effort by Amazonian smallholders: implications for conserving wildlife in mixed-use landscapes - Parry, L.; Barlow, J.; Peres, C.A. (2009)
Most tropical forest landscapes are modified by humans, but the effects of these changes on rural hunting patterns and hunted vertebrate populations remain poorly understood. We investigated subsistence hunting patterns across a highly heterogeneous landscape mosaic in the Brazilian Amazon, where hunters from three villages had access to primary forest, active and fallow agricultural fields, and active and fallow Eucalyptus plantations. Landscape composition and the areas used by hunters were defined using a remote-sensing approach combined with mapping. We quantified hunting effort accounting for the availability and spatial distribution of each habitat. Overall, 71% of the kills were sourced in primary forest, but hunting in primary forest, which was often combined with other extractive activities (such as Brazil nut harvesting), yielded the lowest catch-per-unit-effort of all habitats. Hunting effort per unit area was highest in fallow fields, followed by primary forest, and both of these habitats were over-represented within village hunting catchments when compared to the composition of the available landscape. Active and fallow fields sourced a limited number of species known to be resilient to hunting, but hunting had additional benefits through crop-raider control. In contrast, hunting pressure in active and fallow plantations was low, despite a high catch-per-unit-effort, presumably because there were limited additional benefits from visiting these habitats. These results indicate that large-scale tree plantation and forest regeneration schemes have limited conservation potential for large vertebrates, as they support few forest specialists and fail to attract hunters away from primary forest, (C) 2009 Elsevier Ltd. All rights reserved.